Hubungan Perilaku Kesehatan (Pengetahuan) dengan Kesiapsiagaan Bencana Gempa Bumi dan Tsunami - Sisilia Indriasari Widianingtyas; Michelle Gabriel Lontoh; Yuni Kurniawaty (Universitas Negeri Surabaya, 2024)
Background: knowledge can influence attitudes and awareness of community preparedness. Preparedness is a series of individual and community activities that can respond to disasters appropriately and effectively, especially for people who live in disaster-prone areas. Jember Regency is an area that has a high risk of earthquakes and tsunamis. This study aimed to determine the correlation between knowledge and the level of community preparedness in facing earthquake and tsunami disasters in RW 05 Sidorejo Village, Umbulsari District, Jember. This study aimed to determine the correlation between knowledge and the level of community preparedness in facing earthquake and tsunami disasters. Methods: this study used a correlation design with a cross-sectional approach. The sampling technique used was simple random sampling with a sample size of 42 respondents. The research instrument was a questionnaire to measure respondents' knowledge and individual/household preparedness survey questions from LIPI-UNESCO. The statistical test used in this study was Spearman rank correlations with a significance level of ? = <0.05. Results: the results showed that: there is a moderate positive correlation between knowledge and the level of community preparedness in facing earthquake and tsunami disasters. Conclusions: the level of community preparedness is quite good. However, when viewed from the factor of knowledge about disasters, there are still respondents from low preparedness who have low knowledge about disasters, so efforts are needed to improve community preparedness, namely by increasing knowledge and skills in dealing with earthquake and tsunami disasters through cooperation between the village head and BPBD to conduct disaster preparedness training socialization to the community.